Promotion of West Sumatra Tourism in the Creative Industry and Its Strategic Value in the Language of Promotion - Adjuoktoza Rovylendes; Arnailis Arnailis; Yusnelli Yusnelli; Murniati Murniati; Ferry Herdianto; Nofridayati Nofridayati (Ranah: Jurnal Kajian Bahasa, 2023)
The advancement of tourism in Indonesia has been facilitated through various implicit and nuanced approaches, such as language-based activities and innovative sectors. The availability of promotional texts in the form of language games can be considered a strategic asset, as it can capture the reader's attention and sustain their interest throughout the text, particularly in the context of tourism. The study employed various methodologies such as data acquisition and gathering, data classification and evaluation, and recording the results. A comprehension strategy is a familiar approach wherein we focus on the textual representation of information. The data analysis findings indicate that the utilization of promotional texts in the form of language games possesses a certain degree of strategic significance. This value is exemplified notably through the existence of syntactic deviation, equivocal forms, phonetic wordplay, and the accuracy of vocabulary.  AbstrakKemajuan pariwisata di Indonesia telah difasilitasi melalui berbagai pendekatan implisit dan bernuansa, seperti kegiatan berbasis bahasa dan sektor inovatif. Ketersediaan teks promosi dalam bentuk permainan bahasa dapat dianggap sebagai aset strategis, karena memiliki potensi untuk menarik perhatian pembaca dan mempertahankan minat mereka sepanjang teks, khususnya dalam konteks pariwisata. Studi ini menggunakan berbagai metodologi seperti perolehan dan pengumpulan data, klasifikasi dan evaluasi data, dan pencatatan hasil. Strategi pemahaman adalah pendekatan yang akrab bagi kami, di mana kami memusatkan perhatian kami pada representasi informasi secara tekstual. Temuan analisis data menunjukkan bahwa pemanfaatan teks promosi dalam bentuk permainan bahasa memiliki tingkat signifikansi strategis tertentu. Nilai ini dicontohkan terutama melalui adanya penyimpangan sintaksis, bentuk samar-samar, permainan kata fonetik, dan keakuratan kosa kata.